Metabolomic Profiling of Serum Reveals Energy Metabolism Differences in Nellore Bulls with Divergent Growth Rates during Feedlot Finishing - Moreira, José B. S. [UNESP]; Ribeiro, Richard V. [UNESP]; Cônsolo, Nara R. B.; Ribeiro, Gabriel H.; Colnago, Luiz A.; Torres, Rodrigo N. S. [UNESP]; Neto, Otávio R. Machado [UNESP]; Curi, Rogério A. [UNESP]; Chardulo, Luis Artur L. [UNESP]; Baldassini, Welder A. [UNESP] (American Chemical Society (ACS), 2025)
This study aimed to identify and quantify serum metabolites in beef cattle exhibiting different growth rates during the finishing phase. A total of 120 Nellore (Bos indicus) bulls, averaging 387 ± 14 kg in body weight and 24 ± 2 months of age, were evaluated. The animals were housed for 115 days, and on day 21 (end of the first adaptation step), blood samples were collected from the coccygeal vein for metabolomic analysis. Based on average daily gain (ADG), two contrasting groups were selected: high performance (HP; n = 12) and low performance (LP; n = 12). Serum samples collected on day 21 were analyzed by proton nuclear magnetic resonance (1H NMR) to extract and quantify metabolites. Longissimus muscle area (LMA), backfat thickness (BFT), and hot carcass weight (HCW) were measured via ultrasound at the end of the finishing period. Animal performance was affected by growth rate, with HP animals showing significantly greater final body weight, HCW, and BFT (p < 0.05). A total of 47 serum metabolites were identified, including essential and nonessential amino acids, sugars, peptides, vitamins, amino acid derivatives, and organic acids. HP cattle exhibited higher concentrations of threonine, glycolate, ornithine, histidine, and creatinine (p < 0.05), while LP animals showed greater levels of phenylalanine, succinate, acetate, asparagine, and 2-hydroxyisobutyrate (p < 0.05). Key enriched pathways included the mitochondrial electron transport chain (p = 0.06), ethanol degradation (p = 0.08), and threonine and 2-oxobutanoate degradation (p = 0.09). These findings suggest enhanced energy metabolism in HP animals, driven by greater substrate diversity, while LP animals may exhibit impaired mitochondrial function, negatively impacting performance.